PENGARUH PENGGUNAAN MEDIA KOTAK PERKALIAN TERHADAP HASIL BELAJAR MATEMATIKA MATERI PERKALIAN PADA PESERTA DIDIK KELAS III DI SD KATOLIK BHAKTYARSA MAUMERE - Agneta Kewa Kilok, Yuliana; Kristiani Maria, Sonya; N. Sini Timba, Frederiksen (Jurnal Biogenerasi, 2024)
This study aims to determine the influence of the use of multiplication box learning media in improving student learning outcomes in mathematics learning multiplication material for grade III students of Bhaktyarsa Catholic Elementary School. This study uses quantitative research with a pre-experimental one-group pretest posttest decigen research method. The population in this study is 41 people with a sampling technique using nonprobability sampling techniques. The data collection technique in this study uses tests and observations, with research instruments using test questions and observation sheets. The results of the study showed that the pretest score consisted of a minimum score of 40, a maximum score of 75, a mean value of 57.56 and std. deviation 9.62561. Meanwhile, in the posttest value, a minimum value of 62, a maximum value of 100, a mean value of 84.53 and a deviation of 14.37796 were obtained. The results of this study specifically show that the average posttest score of students increases after using the multiplication box learning media compared to the average pretest score. The data analysis technique used is using paried samples statistical analysis with the help of the IBM SPSS program. The results of the study showed that sig = 0.000 ≤ 0.05, so it was said that there was a very significant difference between the results of the pretest and posttest which indicated that the alternative hypothesis proposed by the researcher was accepted, namely there was a positive influence on the use of multiplication box learning media in improving student learning outcomes in mathematics learning multiplication material for grade III students of Bhaktyarsa Maumere Catholic Elementary School.